A study to evaluate the efficacy and safety of oral fluconazole in the treatment of tinea versicolor - Muhammad, N; Kamal, M; Islam, T; Islam, N; Shafiquzzaman, M (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):31-35. The abstract of this article is available on the PubMed website